Past and Future Climate‐Driven Changes of Agricultural Land in Central Europe - Torbenson, MCA; Esper, J; Brázdil, R; Büntgen, U; Olesen, JE; Semarádová, D; Vlach, M; Urban, O; Balek, J; Kolář, T; Rybníček, M; Pernicová, N; et al. (American Geophysical Union (AGU), 2024)
Abstract Europe is expected to experience major climatic shifts during the 21st century but the impact on agricultural productivity from such changes is uncertain. Here, we combine proxy, instrumental, and model data to assess interannual to multi‐centennial changes in central European agroclimate over the past 2,000 years and projections into the near future. Whereas early 21st century conditions are rare but not fully unprecedented, more than half of the area that was considered highly productive throughout the Common Era in central Europe currently falls outside of that definition. This trend will likely continue as even the most conservative climate projections push central Europe outside the range of past natural variability of changes to agroclimatic zones. Reconstructed extremes prior to the instrumental record align well with contemporary documentary records of societal upheaval. Forecasted changes to the main agroclimatic drivers require substantial adaptation in land use and agricultural management strategies of considerable costs. Plain Language Summary Climate variability has a direct impact on agricultural productivity in Europe. However, to fully understand how this relationship may impact society in the future, we need long‐term records that encompass many different scenarios. We combine stable isotopes from tree rings, instrumental weather data, and climate projections for the future to study the changes occurring within the system over a period of 2,100 years. Periods in the past that experienced harsher agroclimate conditions coincide with societal change or events. The climate projections indicate that more than half of the high‐productivity land within the study region will experience worse conditions in the near future. Key Points More than half of central European land categorized as highly productive in a long‐term context has lost this status due to drought Central European agroclimate is projected to move beyond the conditions of the past 2,000 years in upcoming decades Three previous cases of poor agroclimate conditions have been associated with major societal downturns
Publication status: Published
Keywords: 37 Earth Sciences; 3705 Geology; 13 Climate Action